Hyperelliptic Curves for the Vector Decomposition Problem over Fields of Even Characteristic. (4th March 2015) - Park, Seungkook
Abstract : We present an infinite family of hyperelliptic curves of genus two over a finite field of even characteristic which are suitable for the vector decomposition problem.